2012
DOI: 10.1073/pnas.1209527109
|View full text |Cite
|
Sign up to set email alerts
|

Conserved features of intermediates in amyloid assembly determine their benign or toxic states

Abstract: Some amyloid-forming polypeptides are associated with devastating human diseases and others provide important biological functions. For both, oligomeric intermediates appear during amyloid assembly. Currently we have few tools for characterizing these conformationally labile intermediates and discerning what governs their benign versus toxic states. Here, we examine intermediates in the assembly of a normal, functional amyloid, the priondetermining region of yeast Sup35 (NM). During assembly, NM formed a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
127
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 35 publications
(78 reference statements)
5
127
0
Order By: Relevance
“…In cases of extensive OPA, increasing the protein concentration may even prolong the duration of the lag phase and decrease the amyloid aggregation rate. This angle of approach is, to our knowledge, totally original because the main focus has been on the detection and morphological/ toxicological characterization of the amorphous precipitates (4,7,8,9,14). The new possibility of estimating the relative amounts of off-pathway and amyloid aggregates accentuates the need for cataloguing the deleterious species in each disease.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of extensive OPA, increasing the protein concentration may even prolong the duration of the lag phase and decrease the amyloid aggregation rate. This angle of approach is, to our knowledge, totally original because the main focus has been on the detection and morphological/ toxicological characterization of the amorphous precipitates (4,7,8,9,14). The new possibility of estimating the relative amounts of off-pathway and amyloid aggregates accentuates the need for cataloguing the deleterious species in each disease.…”
Section: Discussionmentioning
confidence: 99%
“…69 Of note, a variety of amyloid proteins and peptides with different primary structures form oligomers with similar quaternary structures. 8,10 These structures are more stable than their monomeric and smaller oligomeric precursors, but less stable than their ultimate fibrillar products. 11,12 From a structure-function perspective, toxic oligomers would be predicted to have relatively well-organized structures that interact with cellular membranes, receptors, or other proteins.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, mass spectrometry coupled with ion mobility spectrometry (IM-MS) experiments have provided information regarding the size and shape of the lowmolecular-weight oligomeric forms of Aβ and other amyloidoic proteins (6, 7). A variety of biophysical methods have been used to study the oligomers extensively (2,(7)(8)(9)(10)(11)(12)(13)(14).Despite such studies, the ability to measure the rates of formation of the oligomers remains difficult. Recently, Lee et al (15) reported a method suitable for monitoring the full time course of aggregation showing distinct phases corresponding to oligomerization and fibrillization using Cys-Cys-Aβ and FlAsH dye binding to tetracysteine motifs arising from self-association of Aβ.…”
mentioning
confidence: 99%
“…More recently, mass spectrometry coupled with ion mobility spectrometry (IM-MS) experiments have provided information regarding the size and shape of the lowmolecular-weight oligomeric forms of Aβ and other amyloidoic proteins (6, 7). A variety of biophysical methods have been used to study the oligomers extensively (2,(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%